Satisfaction level of employees at University Centers from a Distance State University in Costa Rica (UNED Research Journal, 2019)
Introduction: Personal satisfaction has been studied since 1930 and several theories have emerged, however, all conclude that satisfaction is subjective and depends on extrinsic and intrinsic factors of each individual. Objective: to measure satisfaction with life, work and country in the staff of a Costa Rican university. Methods: A questionnaire was applied online  from October 2017 to October 2018. Satisfaction was measured in three dimensions: aspects of life, work and national scope. Results: 363 staff members from 39 university centers answered. Their Personal Satisfaction Index is generally high, particularly for respondents in rural settings, those over 40 years old and those who have been more time in their job positions. Conclusions: age, time in job and rural settings correspond with the lever of personal satisfaction.
Keywords: quality of life; happiness; well-being; perception; goals; achievements